Teachers’ language teaching efficiency and learners’ English proficiency: Basis for an intervention program in Ocampo district - Bonita, Marian Grace D. (Universitas Ahmad Dahlan, 2025)
Reading proficiency remains a critical challenge among Grade 3 learners in the Crossroad Sector of the Ocampo District, prompting the need to investigate contributing factors and develop targeted interventions. This study aimed to determine the influence of teachers’ language teaching efficiency on learners’ English learning proficiency and use the findings to craft an evidence-based intervention program for the 2023–2024 academic year. Specifically, it examined (1) the level of teachers’ language teaching efficiency, (2) learners’ learning proficiency, (3) the difference in learners’ reading performance between pre-test and post-test, (4) the relationship between teaching efficiency and learning proficiency, (5) the extent to which teaching efficiency influences learners’ proficiency, and (6) proposed an intervention program to address identified gaps. Utilizing a descriptive-comparative-correlational research design, data were collected through the Comprehensive Rapid Literacy Assessment and survey questionnaires. Statistical tools such as Weighted Mean, Pearson’s r, and Coefficient of Determination were applied. Findings revealed that teaching efficiency was generally rated as “Much Evident,” and significant improvements in word recognition were observed post-intervention. A strong correlation was found between teaching efficiency and learners’ proficiency in English. However, teacher–learner interaction was identified as a weak area. Based on these results, an intervention program was proposed to enhance reading fluency and comprehension.